Theoretical Foundations of the Professional Training of a Future Teacher Based on the Competence Approach - Mykola Balukh (Pedagogical Discourse, 2022)
The article studies the essence of the concept of «professional competence of a future teacher».It was determined that, in a broad sense, competence is interpreted as a level of the formation of person’s social and practical experience, a level of learning social and individual forms of activity, which enables the individual to function successfully in the society within the limits of his abilities and status. Competence is the ability to solve professionally and effectively certain problems that arise during the life of any person.Analysis of the approaches to the definition of the concept of competence suggested by other authors in the psychological and pedagogical literature was carried out. It was concluded that the existing interdisciplinary exchange of opinions regarding the understanding of "competence" enables researchers to substantiate and form a new meaning of the concept, based on the goals and interests of certain studies.The structure of the competences is defined as internal, potential, hidden psychological newly obtained knowledge, skills, action algorithms, systems of values and relationships that manifest themselves in human competence.On the basis of theoretical and empirical studies, it was analyzed that professional competence is a subject of special study. Four blocks in the structure of the concept are systematized: professional, psychological and pedagogical knowledge; professional pedagogical skills; professional psychological attitudes and settings of a teacher; personal qualities that ensure the mastery of professional knowledge and skills by the teacher.It was established that the systemic characteristics of teacher's professional competencies are his personal qualities (pedagogical self-awareness, individual style, creativity), pedagogical knowledge, pedagogical thinking, pedagogical intuition, pedagogical improvisation, pedagogical imagination, pedagogical optimism, pedagogical reflection, mastering of which in the complex contributes to the teacher's implementation of the functions of an educator, diagnostician, self-diagnostician, methodologist, the subject of the pedagogical work, which are  important components of professional competencies.